ANTIBACTERIAL POTENTIAL OF RED BETEL LEAVES (Piper crocatum Ruiz and Pav) - Kumara Dewi Ni Wayan Rika; Ugrasena Putu Yudha; Puspita Sari Dyah Ratna Ayu (Journal Pharmactive, 2023)
Background: Red betel leaf (Piper crocatum Ruiz and Pav.) is one of the medicinal plants which empirically has the efficacy of healing spiritual ailments. The secondary metabolite compounds contained in red betel leaves are essential oils, flavonoids, alkaloids, saponins, tannins, terpenoids, and phenolic compounds which have antibacterial activity. Objective: To determine the antibacterial potential of red betel leaves (Piper crocatum Ruiz and Pav.) Method: This study uses a descriptive method using a structured article review method. Data collection was carried out using the Google Scholar database, Science Direct and PubMed with keywords “Piper crocatum Ruiz and Pav”, “Piper crocatum”, “Screening phytochemical”, Piper crocatum”, “Leaf Piper crocatum”, and “antibacterial Piper crocatum”. Results: Based on literature studies, the antibacterial potential of red betel leaves (Piper crocatum Ruiz and Pav.) can be seen from the inhibition zones produced for both gram-positive and gram-negative bacteria, although with different values of the resulting inhibition zones.